Investment aftercare matters - Carolina Arriagada Peters (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2020)
Investment aftercare services are a must-have feature for investment promotion agencies that are serious about maximizing the impact of FDI. Government should review their existing practices and help investors grow their business, champion local opportunities and further develop the host economy.
Keywords: 330